Complete chloroplast genome of a rare deciduous tree species, Sinomanglietia glauca (Magnoliaceae). Issue 2 (3rd July 2019) - Li, Jiang-Ping; Cui, Ling; Qiu, Li-Hong; Guo, Chun-Ce; Yang, Guang-Yao; Zhang, Wen-Gen
Abstract: The complete chloroplast genome of a rare deciduous tree species with ornamental value, Sinomanglietia glauca, was first determined. It was 160, 170 bp in length, including a pair of inverted repeat (IR, 26, 567 bp) regions separated by a small single copy (SSC, 18, 842 bp) sequence and a large single copy (LSC, 88, 194 bp) sequence. The chloroplast genome contained 132 genes, consisting of 87 CDS, 8 rRNA genes, and 37 tRNA genes. Thirty-four SSR sites were detected in the chloroplast genome. The phylogenetic analysis revealed that all sampled Manglietia species were clustered together, and S. glauca was placed as sister to the clade Manglietia, indicated that the genus Sinomanglietia may be legitimate and should be recovered.